Gastrointestinal parasites in swine raised in family farming in Patos de Minas – MG region (Research, Society and Development, 2022)
In families living in the rural area of the municipality of Patos de Minas – MG, subsistence pig farming is a very common activity. This research aimed to verify the incidence of gastrointestinal parasites in pigs from this type of breeding in the region; carry out parasite identification through swine feces collected from selected properties; and describe the pathogenesis of the parasites found and the sanitary management practiced by the producers. Samples from 43 pigs (males and females, from 60 days old) kept in domestic farms in 10 properties, were analyzed using the Willis-Mollay method. Of the collected samples that obtained findings, it was found that 48% were eggs of Oesophagostumum spp, 10% Acaris suum, 5% Ascarops strongylina, 8% Isospora, 5% Ascarops strongylina, 3% Strongyloides ransomi, 2% of Metastrongylus apri and 1% Thrichuris suis. Were foud too 8% of oocystis Isospora, 5% of Eimeria sp. and 17% of cystis of Balantidium coli. Given the reality found, it is concluded that there is a need for periodic performance of parasitological examinations, treatment of infected animals and guidance of breeders in order to carry out an adequate sanitary management.